Implementation of the Gender Mainstreaming Program in South Kalimantan Province - Mudzrika, Nadzira Auliya; Irwansyah, Irwansyah; Syafari, Muhammad Riduansyah (PT. Riset Press International, 2025)
This study aims to examine the implementation of the Gender Mainstreaming Program (PUG) in South Kalimantan Province by exploring stakeholders’ understanding, institutional awareness of the importance of gender perspectives, and the key challenges that affect the effectiveness of the program. It also seeks to explain how institutional capacity, structural factors, and cultural dynamics support or hinder the success of PUG. A qualitative approach with a case study design was used. Data were collected through in-depth interviews with key informants from relevant agencies (DP3AKB, BAPPEDA, BPKAD, and the Inspectorate), document analysis, and review of planning documents and Gender Responsive Budgeting (PPRG) evaluations for the 2023–2024 fiscal year. Data were analysed thematically using George C. Edwards III’s policy implementation framework, which includes communication, resources, disposition of implementers, and bureaucratic structure. The findings indicate that most agencies demonstrate an awareness of the importance of integrating gender into development policies, although such awareness remains largely normative and has yet to reach a transformative level. Key obstacles include limited human resource capacity, insufficient sex-disaggregated data, weak cross-sectoral coordination, and bureaucratic cultures that are not yet fully gender-inclusive. In conclusion, the implementation of PUG in South Kalimantan remains at a procedural stage and requires strengthened institutional capacity, improved gender data systems, and enhanced regulatory and cross-sector coordination to ensure its sustainable and effective implementation.